2016
DOI: 10.1111/echo.13396
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of right ventricular contractile reserve in healthy subjects

Abstract: Our results provide age- and sex-related limits of normal for RV contractile reserve as assessed by exercise stress echocardiography and demonstrate that RV systolic function indices (PASP, TAPSE, S', and TAPSE/PASP) correlate with maximum exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
6
23
2
Order By: Relevance
“…The limits of normal of the indices of RV function during exercise are less well known. The increases in sPAP/ESA and decreases in TAPSE/sPAP found with cycling in the present study agree with previously reported values [7,14]. Large increases in TAPSE, S (tricuspid annulus tissue Doppler velocity), FAC and sPAP/ESA during cycle ergometry again point at this purely dynamic maximum exercise test as being preferable for exercise stress testing of the RV.…”
supporting
confidence: 92%
“…The limits of normal of the indices of RV function during exercise are less well known. The increases in sPAP/ESA and decreases in TAPSE/sPAP found with cycling in the present study agree with previously reported values [7,14]. Large increases in TAPSE, S (tricuspid annulus tissue Doppler velocity), FAC and sPAP/ESA during cycle ergometry again point at this purely dynamic maximum exercise test as being preferable for exercise stress testing of the RV.…”
supporting
confidence: 92%
“…Recently, D'Alto et al demonstrated that echocardiographic RV systolic function indices (tricuspid annular plane systolic excursion (TAPSE), S′, and TAPSE/PAP) correlate with maximal workload in healthy subjects. This finding illustrates that a higher RV contractility reserve, defined as the difference between peak exercise and rest, is an advantage to reach high exercise levels and suggests a potential role of the RV in exercise capacity limitation [13].…”
Section: Right Ventriclementioning
confidence: 71%
“…However, RV anatomical and physiological properties are maybe not designed to face dramatical afterload increase at high levels of exercise. As compared to the left ventricle (LV), load increases are greater for the RV during exercise [12], and its contractile reserve may become insufficient for adequate blood supply to peripheral demand [12,13]. Relative to the LV, the greater load that the RV faces during exercise is dominantly attributed to a larger exercise-induced increase in pulmonary artery pressure (PAP) relative to systemic vascular pressure [3].…”
Section: Right Ventriclementioning
confidence: 99%
“…They found a blunted increase in cardiac index response to exercise which is a crucial determinant of exercise capacity and clinical outcome in precapillary PH. In a study performed in healthy subjects using ESE, RV contractile reserve (∆PASP, ∆SV, ∆S′, ∆TAPSE/PASP) was associated with maximum exercise capacity (defined as the maximal workload) . In a small‐scale study by Sharma et al, RV contractile reserve (∆S′ and ∆SV) was shown to correlate with exercise capacity (assessed by CPET) of patients with pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 96%
“…18,19 Peak VO 2 is the most widely used parameter of exercise capacity and provides prognostic information. 20 25 In a small-scale study by Sharma et al, 26 RV contractile reserve (∆S′ and ∆SV) was shown to correlate with exercise capacity (assessed by CPET) of patients with pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 98%